PENGARUH IKLIM KOMUNIKASI DAN NILAI-NILAI BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI PERGURUAN TINGGI SWASTA - Harti Yuwarti (Universitas Prof. Dr. Moestopo (Beragama), 2018)
This study aims to determine the effect of the communication climate on the performance of employees, to determine the effect of organizational cultural values on the performance of Moestopo University employees and to determine the effect of the communication climate and organizational cultural values on the performance of Moestopo University employee. This research uses a quantitative approach and the results of the research are carried out by using multiple correlation tests, multiple linear regression tests and T tests. In testing the hypothesis, climax of Organizational Communication partially have a positive and significant effect on Employee Performance. Organizational Culture partially has a positive and significant effect on Employee Performance. Based on the results of the simultaneous test obtained the Organizational Communication Climate and Organizational Culture simultaneously have a positive and significant effect on employee performance. The percentage contribution of the independent variable (Organizational Communication Climate and Organizational Culture) to the dependent variable (employee performance) has a power of 65.4% or the variation of the independent variables used in the model (Organizational Communication Climate and Organizational Culture) able to explain 65.4% of the dependent variable (employee performance ) While the determination coefficient value is 0.654 which is closer to number 1, it can be concluded that the level of the relationship is quite strong.